ROSELA (HIBISCUS SABDARIFFA) MENCEGAH KENAIKAN TEKANAN NADI KENAIKAN MALONDIALDEHIDE DAN MENINGKATKAN STATUS ANTIOKSIDAN TOTAL TIKUS YANG DIINDUKSI ALKOHOL - Budi Siswanto; Denny Agustiningsih; Setyo Purwono (Jurnal Obstretika Scientia, 2014)
Oxidative stress can cause coronary heart disease. This research aims to study the effect of steeping rosella flower petals showed differences in pulse pressure, plasma MDA and SATs in the blood of rats fed 20% alcohol dose 4 grams/kg body weight/day as a trigger of reactive oxygen species. Thirty male wistar rats at least 150 grams of body weight divided into five groups, each group of six rats. Group A was given boiled water, group B was given alcohol, groups C, D and E are given alcohol and rosella. Dose of 0.75 grams rosella rosella in 200 cc of the water brewing given to kelompom C, while group D rosella dose 1.5 g and E 3 gr. Giving rosella and alcohol for 70 days by way of the sonde. Rosella alcohol given at 7:00 and 11:00 hours. Pulse pressure, plasma MDA and plasma levels of SAT were measured before and after treatment. The results showed that pulse pressure, plasma MDA steeping rosella groups given 0.75 g, 1.5 grams and 3 grams of lower and higher SAT levels compared with groups given alcohol alone. Conclusion rats fed steeping rosella flower petals and alcohol pulse pressure, lower levels of plasma MDA and higher SAT levels compared with groups that were given alcohol alone.